Studi Kasus: Peran Tahkim, Ijtihad, dan Fatwa dalam Reformasi Sistem Peradilan Islam di Pengadilan Agama Indonesia - Nabila Azizah; Ripani Ripani; Muhammad Balya; Muhammad Jaidi (Sharia Faculty of Universitas Islam Negeri Maulana Malik Ibrahim Malang, Indonesia, 2026)
This study aims to analyze judicial ijtihad, the role of fatwas as a basis for legal reasoning, and the application of tahkim and mediation in the Religious Courts of Indonesia. The background of this research lies in the increasing complexity of cases that cannot be fully addressed by positive law, thus requiring a more adaptive and integrative approach. This study employs a qualitative method with a case study approach, utilizing court decisions, interviews with judges and mediators, and analysis of fatwas and Islamic legal literature. The findings reveal that judges do not solely rely on statutory regulations but also exercise ijtihad by integrating fiqh principles and fatwas as normative justification. Furthermore, tahkim and mediation play a significant role in resolving disputes in a peaceful and efficient manner. These findings indicate an integrative pattern in the practice of Religious Courts, combining normative, substantive, and solution-oriented approaches. Therefore, this study concludes that Religious Courts in Indonesia are evolving adaptively to meet societal needs.